Audiovisual Temporal Processing and Synchrony Perception in the Rat - Schormans, Ashley L.; Scott, Kaela E.; Vo, Albert M. Q.; Tyker, Anna; Typlt, Marei; Stolzberg, Daniel; Allman, Brian L. (Frontiers in Behavioral Neuroscience, 2017)
Extensive research on humans has improved our understanding of how the brain integrates information from our different senses, and has begun to uncover the brain regions and large-scale neural activity that contributes to an observer’s ability to perceive the relative timing of auditory and visual stimuli. In the present study, we developed the first behavioral tasks to assess the perception of audiovisual temporal synchrony in rats. Modeled after the parameters used in human studies, separate groups of rats were trained to perform 1) a simultaneity judgement task in which they reported whether audiovisual stimuli at various stimulus onset asynchronies (SOAs) were presented simultaneously or not, and 2) a temporal order judgement task in which they reported whether they perceived the auditory or visual stimulus to have been presented first. Furthermore, using in vivo electrophysiological recordings in the lateral extrastriate visual (V2L) cortex of anesthetized rats, we performed the first investigation of how neurons in the rat multisensory cortex integrate audiovisual stimuli presented at different SOAs. As predicted, rats (n=7) trained to perform the simultaneity judgement task could accurately (~80%) identify synchronous versus asynchronous (200 ms SOA) trials. Moreover, the rats judged trials at 10 ms SOA to be synchronous, whereas the majority (~70%) of trials at 100 ms SOA were perceived to be asynchronous. During the temporal order judgement task, rats (n=7) perceived the synchronous audiovisual stimuli to be “visual first” for ~52% of the trials, and calculation of the smallest timing interval between the auditory and visual stimuli that could be detected in each rat (i.e., the just noticeable difference) ranged from 77 to 122 ms. Neurons in the rat V2L cortex were sensitive to the timing of audiovisual stimuli, such that spiking activity was greatest during trials when the visual stimulus preceded the auditory by 20 to 40 ms. Ultimately, given that our behavioral and electrophysiological results were consistent with studies conducted on human participants and previous recordings made in multisensory brain regions of different species, we suggest that the rat represents an effective model for studying audiovisual temporal synchrony at both the neuronal and perceptual level.